Sacral Stress Fracture in an Amateur Badminton Player. (3rd October 2017) - Yuasa, Yusuke; Miyakoshi, Naohisa; Hongo, Michio; Ebata, Kunio; Tomioka, Tatsuru; Shimada, Yoichi
Abstract : Sacral stress fractures are rare among athletes but have been reported most frequently in long distance runners. We report herein the first case of a sacral stress fracture in an amateur badminton player. A 16-year-old, left-handed adolescent girl, who had just started to play badminton 3 months previously, complained of acute left buttock pain when she received a shuttlecock. Magnetic resonance imaging revealed a linear lesion of the left sacrum with low signal intensity on T1- and high signal intensity on T2-weighted images, which was consistent with a stress fracture. Conservative treatment with rest relieved her symptoms. Her fracture was considered to have occurred due to repetition of an exercise that caused excessive vertical power.